The poetry of Ahmed bin Al-Muadhal Al-Basristudy, Acollection , and examination The rest of it - أ.م.د لؤي سلمان راضي (Journal of College of Education, 2023)
Ahmed bin Al-Muadhl Al-Basri Abbasid poet Has little poet lived in the third century AH, was a scholar jurist and writer eloquent, descended from an ancient family in the loan of poetry, has devoted this research to take care of the collection of what reached us from his poetry scattered in the sources, due to his scientific status and literary ability, envisaging the definition of this aspect of his personality, and document the rest of his poems reflected in which his talent on the one hand and his clear tendency - on the other hand - towards the topics of wisdom and asceticism consistent with his moral qualities, As well as other traditional purposes on various occasions